PTU-078 Efficacy of High and low dose Oral Vitamin D Replacement Therapy in Inflammatory Bowel Disease: Single Centre Cohort. (4th June 2013) - Hiew, H J; Naghibi, M; Wu, J; Saunders, J; Cummings, F; Smith, T R
Abstract : Introduction: Inflammatory bowel disease (IBD) patients are at risk of micronutrient deficiencies, including vitamin D. There is increasing evidence that vitamin D deficiency has a negative impact on disease activity. This study aims to determine the vitamin D status of a sub-set of IBD patients at a University Hospital and to evaluate the effectiveness of oral vitamin D treatment in correcting the deficiency. Methods: All IBD patients with recorded serum vitamin D levels measured in 2011 were identified. Vitamin D deficiency was determined as combined vitamin D2 and D3 plasma levels lower than 52 nmol/L and treatment response was assessed up to 4–6 months after initiation of oral treatment. Oral vitamin D supplementation was classified as 'low dose' when patients prescribed daily 800 units of vitamin D2 or D3 and classified as 'high dose' when given either 100'000 units once only or 50'000 units per week for 6 weeks. Results: 205 IBD patients with plasma vitamin D measurements were identified, 95 (46%) were found to be vitamin D deficient. There was no significant difference in the prevalence of vitamin D deficiency between the Crohn's disease (CD) and ulcerative colitis (UC) patients, 44% vs 50%, (p = 0.449). 50/95 (52.6%) patients received treatment and 32 treatment episodes had follow up vitamin D status measurement within 4–6 months. Those who received 'high dose' oral vitamin D demonstrated an increase in vitamin D levels of 150% after treatment compared to an increase of 34% in those put on 'low dose' vitamin D supplement (p = 0.001). There was no significant difference in treatment response between CD and UC (p = 0.874) (see table 1). Conclusion: There were no differences in plasma vitamin D concentrations between patients with CD and UC. Oral vitamin D replacement is an effective treatment for vitamin D deficiency in IBD patients and appears to be dose responsive; irrespective of whether patient have UC or CD (including small bowel disease). The optimal dose of oral vitamin D supplementation is yet to be determined, but higher doses are significantly more effective. Disclosure of Interest: None Declared